THE PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITY TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - Hotma Mentalita (Akuntansi Prima, 2020)
This research aim is to analyze how the Good Corporate Governance and Profitability influence the Earning Management in the Manufacture Companies listed in the Indonesian Stock Exchange. Explanatory Method was used for this research. It used 144 manufacture companies as population and 106 of them used as the samples taken by using proportional random sampling technique. Data were gathered by conducting documentary study and analyzed by using panel data regression analysis. The result of the research showed that, simultaneously, Good Corporate Governance and Profitability had the influence on Earning Management. Partially, Good Corporate Governance did not have any influence on Earning Management, while Profitability had the influence on Earning Management.